Functional Characteristics of Inorganic Pyrophosphatase from Psychrotroph Shewanella sp. AS-11 upon Activation by Various Divalent Cations - Ginting1, E.L.; Maeganeku2, C.; Motoshima2, H.; Watanabe1, K. (Asian Journal of Chemistry, 2014)
Inorganic pyrophosphatase (PPase) is an essential enzyme in all living organisms, as it hydrolyzes inorganic pyrophosphate (PPi) to phosphate (Pi). Inorganic pyrophosphatase are only active in the presence of metal ion cofactors. This research investigated effects of various divalent cations on the functional characteristics of psychrotroph Shewanella sp. AS-11 (Sh-PPase). The results showed Co2+, Mn2+ and Zn2+ markedly activated the enzyme. The optimal temperature for activity of Sh-PPase activated by Mn2+ was surprisingly low (5 °C), while those of Zn, Co and Mg-activated enzymes were 20, 30 and 40 °C, respectively. The specific activities of Sh-PPases activated by Co2+, Mn2+ and Zn2+ were 100-, 45- and 12-fold higher than Mg-activated Sh-PPase at 5 ºC, respectively. Sh-PPase activated by Co2+ or Mn2+ was stable up to 40 ºC and activated by Zn2+ up to 50 ºC. Activation of Sh-PPase with Co2+, Mn2+ and Zn2+ enhanced kcat, but did not significantly affect Km. Thus divalent cations markedly influenced the catalytic efficiency, temperature dependency and thermo-stability of Sh-PPase. Mn2+ or Co2+ ions are required to gain cold-adapted characteristics.